Quelques exemples d'apports des manuscrits de Qumrân à l'étude du judaïsme ancien - Puech, Émile (Revue biblique, 2012)
Les différences d’interprétations de la loi sabbatique et des formules d’exorcismes dans les manuscrits et dans le Nouveau Testament expliquent en partie les motifs d’accusation retenus pour la crucifixion de Jésus, crucifixion du coupable vivant selon la lecture ancienne de Dt 21,22-23, comme le soulignent plusieurs manuscrits qumraniens.\n4207 The diversities of interpretations of the sabbatical law and of the formulae of excorcisms in the manuscripts and in the New Testament explain in part the causes of the indictment by which Jesus was condemned to crucifixion. This was the Jewish punishment on a cross of a living man according to Dt 21:22-23, as it appears in several manuscripts from Qumran.\n4207 \n4207